Identification of Linguistic Markers of Insight and Intuition Using Computer‐Assisted Text Analysis. (10th December 2021) - Sadler‐Smith, Eugene; Akstinaite, Vita
ABSTRACT: Insight and intuition are important concepts in creativity research and creative behavior with applications in a wide variety of professional and business domains. Understanding and articulating their similarities and differences is important theoretically and practically. Researchers and practitioners can benefit from the application of new techniques which can distinguish between these two phenomena based on individuals' subjective experiences as articulated in written or spoken accounts. Subtle language cues provide objective, quantifiable data (linguistic markers) to identify and analyze a variety of cognitive and affective psychological processes. Computer‐assisted text analysis (CATA) based on the theory of natural language use offers researchers a systematic and objective framework for extracting and interpreting such markers. This Brief Report proposes the use of CATA for the identification of the linguistic markers of insight and intuition and outlines ways in which the method could be applied in future research. Using CATA, it was possible to identify a preliminary set of linguistic markers which could be used to distinguish between insight and intuition.